Psycholinguistic features of communication in English and Uzbek (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article investigates the psycholinguistic features of communication in English and Uzbek, emphasizing the cognitive and psychological processes that shape language production and comprehension. It explores how cultural context, thought patterns, memory, and perception influence verbal interaction and message interpretation. By comparing English, a Germanic language with analytic structures, and Uzbek, a Turkic language with agglutinative morphology, the study highlights differences in lexical access, sentence processing, and pragmatic cues. Additionally, it examines bilingualism and code-switching among Uzbek-English bilingual speakers to understand their impact on emotional expression and cognitive load. The findings offer insights into intercultural communication, language acquisition, and applied psycholinguistics.